2018
DOI: 10.36233/0372-9311-2018-4-107-113
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Physiological Characterization of a Consortium of Hydrocarbon-Oxidizing Bacteria of Oil and Oil Products

Abstract: A consortium of microorganisms were isolated from TC-1 fuel form, each member of which is capable of consistently degrade hydrocarbons’ different fractions. The 5 strains of hydrocarbon-oxidizing bacteria (PSB) were identified and isolated from TS-1 jet fuel. Their physiological and biochemical features are defined. All strains exhibit positive catalase activity. It is determined that all UOB strains, producing exogenous and endogenous surfactants, are capable to growth on media with different fraction of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In our previous works, thirteen bacterial strains were isolated from the contaminated TS-1 aviation kerosene by conventional microbiological methods on the Rich medium. Their taxonomic affiliation was verified by 16S rRNA sequencing [ 45 , 46 ]. Kerosene was characterized by a diverse bacterial composition that included the following genera: Sphingobacterium, Alcaligenes, Rhodococcus, and Deinococcus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous works, thirteen bacterial strains were isolated from the contaminated TS-1 aviation kerosene by conventional microbiological methods on the Rich medium. Their taxonomic affiliation was verified by 16S rRNA sequencing [ 45 , 46 ]. Kerosene was characterized by a diverse bacterial composition that included the following genera: Sphingobacterium, Alcaligenes, Rhodococcus, and Deinococcus .…”
Section: Discussionmentioning
confidence: 99%
“…Kerosene was characterized by a diverse bacterial composition that included the following genera: Sphingobacterium, Alcaligenes, Rhodococcus, and Deinococcus . Isolated strains were capable of the degradation of hydrocarbons and production of biosurfactants [ 45 , 46 ]. At the same time, in this study, the same bacterial genera were indicated in monospore fungal cultures based on 16S rRNA metabarcoding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important factors determining the effectiveness of the use of micromycetes as oil utilizers are their active enzymatic system and high viability in conditions of oil contamination [56]. Micromycetes-destructors of petroleum hydrocarbons include at least 100 species of microscopic fungi [57]. Patent documents for bioremediation techniques (most of them from China, the USA, Japan, and Taiwan [27]) mention more than 30 species of fungi.…”
mentioning
confidence: 99%